Avaliação dos efeitos de PCHs em cascata na qualidade de água de um rio afluente do Pantanal com monitoramento de alta frequência - Silva, Antonio Carlos Coelho da (2021)
This study seek to evaluate the possible changes in water quality due to hydroelectric projects at rivers on the edge of the Pantanal. Based on the analysis of 7 (seven) water quality variables (pH, OD, Temperature, Conductivity, Turbidity, Nitrate and Carbon), measured in sub-hourly resolution, the system composed of three automatic stations monitors the Ponte de Pedra stream , upstream and downstream of the SHPs, and constitutes the first high-frequency monitoring system for water quality parameters in a contributing river in the Pantanal. In the statistical analyses, the influence of the flow, the correlations between the monitored parameters, the analysis of principal components, and the analysis of variance were evaluated, which took into account the location of the monitored points, the period of the day, the months of the year and the dry and wet seasons. The results of high-frequency monitoring showed that there is no significant change in the monitored variables during periods of the day. However, despite the low nutrient and sediment load of the stream, the results showed significant differences between the dry and wet seasons in the downstream and upstream points of the SHP, in important parameters such as hydrogen potential and dissolved oxygen. Of the variables evaluated, temperature had a cumulative impact that can be associated with the cascade effects of hydroelectric plants. Although small, the reservoir retains a carbon and nitrogen charge. High-frequency monitoring is very efficient to show rapid changes in water quality, due to hydropics produced by the operation of small hydroelectric plants.